APLIKASI PENGENALAN TEKNIK DASAR BELADIRI SHORINJI KEMPO BERBASIS ANDROID: APPLICATION OF INTRODUCTION TO BASIC MARTIAL TECHNIQUES SHORINJI KEMPO BASED ON ANDROID - Marlinda Sanglise; Helmi Saputra (Universitas Papua, 2018)
The interest of the people in Indonesia towards the Kempo sport continues to increase.But in the campo training in Indonesia there are still many shortcomings felt by thetraining students, such as the names of techniques that are difficult to memorize, toomuch material, lack of clarity about the details of each movement, and lack of learningmedia. Based on this, an Introduction to the Android-Based Shorinji Kempo BasicTechnique Application was designed, named the Mobile Learning Kihon ShorinjiKempo. This application was made as a medium for learning alternative to learning.This application is made with Java programming language as the source engine andLanguages Markup Extension as an interface that runs on android smartphones. Theapplication was stated to be successfully built by providing information on basictechniques, through the questionnaire results conducted on 5 respondents of campstudents and 5 respondents of the general public, 54% of respondents agreed and 46%of respondents strongly agreed the Kihon Shorinji Kempo Mobile Learning applicationwas spread as media alternative learning basic techniques.